Book review: Rethinking residential child care: Positive perspectives. Mark Smith Bristol, Policy Press, 2009 - Zachari Duncalf (Scottish Journal of Residential Child Care)
A review of Rethinking residential child care: positive perspectives by Mark Smith (2009). Bristol: The Policy Press, ISBN 978-1-86134-908-8.